Studies in law, politics, and society. Vol. 45 - Sarat, Austin (Studies in law, politics, and society ;, 2008)
This forty-fifth volume of "Studies in Law, Politics, and Society" brings together the work of scholars from several disciplines, work which usefully illuminates central questions surrounding the operation of law and legal systems. Their work offers new perspectives on sentencing and punishment, lawyering for the public good, and the meaning of legal doctrine. The articles published here exemplify the exciting and innovative work now being done in interdisciplinary legal scholarship.